2001
DOI: 10.1001/archotol.127.9.1083
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Botulinum Toxin Treatment for Patients With Spasmodic Dysphonia

Abstract: Spasmodic dysphonia has a significant impact on patients' perception of quality of life as measured by the VHI. Significant improvements in all 3 subscale scores and the total score on the VHI occur after treatment with botulinum toxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
3
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 12 publications
2
38
3
6
Order By: Relevance
“…The clinician needs information from traditional impairment or activity-based measures such as videostroboscopy and voice quality ratings, as well as information from the patient regarding his or her experiences with the physical, personal and social manifestations of the disorder. Although existing voice-related instruments document psychosocial consequences of SD (Benninger et al, 2001;Courey et al, 2000;Hogikyan et al, 2001;Rubin et al, 2004), results from the present study, based on the insider's perspective, suggest that there is still room for further work in this area.Using a different methodology, this study has explored the biopsychosocial consequences of SD and has highlighted three issues in understanding communication-related QOL that warrant The second issue raised by this study is that the unique relationships among the components of the model must be identified for each client. While all the components of the model were relevant to some degree for each participant in this study, there were widely varying patterns among participants in terms of what issues contributed most to communication-related QOL, and how these issues interacted for each person.…”
contrasting
confidence: 61%
See 2 more Smart Citations
“…The clinician needs information from traditional impairment or activity-based measures such as videostroboscopy and voice quality ratings, as well as information from the patient regarding his or her experiences with the physical, personal and social manifestations of the disorder. Although existing voice-related instruments document psychosocial consequences of SD (Benninger et al, 2001;Courey et al, 2000;Hogikyan et al, 2001;Rubin et al, 2004), results from the present study, based on the insider's perspective, suggest that there is still room for further work in this area.Using a different methodology, this study has explored the biopsychosocial consequences of SD and has highlighted three issues in understanding communication-related QOL that warrant The second issue raised by this study is that the unique relationships among the components of the model must be identified for each client. While all the components of the model were relevant to some degree for each participant in this study, there were widely varying patterns among participants in terms of what issues contributed most to communication-related QOL, and how these issues interacted for each person.…”
contrasting
confidence: 61%
“…Smith et al (1998) reported that weak and hoarse voice qualities were the second and third most common symptoms of SD respectively. Several studies have demonstrated that participants generally rate their voices as moderately to severely affected by SD (Aronson et al, 1993;Benninger et al, 2001;Blitzer et al, 1998;Hogikyan et al, 2001;Langeveld, Luteijn et al, 2001;Langeveld, van Rossum et al, 2001;Rubin et al, 2004;Schonweiler, Wohlfarth, Dengler, & Ptok, 1998).…”
Section: The Insider's Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Speyer [18] reported a non-signiWcant median improvement of 6 points after voice therapy in patients with a diversity of chronic benign voice disorders. Other studies on the eVect of several medical treatment modalities for diVerent benign voice disorders show a mean VHI improvement ranging from 13 to 46 points [2,13,26]. All these studies on the eYcacy of voice intervention on various voice patient groups reveal that a statistical diVerence score is at least 12 points.…”
Section: Discussionmentioning
confidence: 91%
“…Neste estudo, quando comparado com outras pesquisas, não se encontrou diferença quanto à melhora entre os gêneros (Lindestad et al, 1997;Eadi et al, 2007;Elmiyeh et al, 2010), porém deve-se ter em conta que existe maior número de mulheres com DL do que homens. Alguns estudos realizaram exames de espectrografia de banda larga (Rees et al, 2007) e banda estreita (Ludlow et al,1988;Gama et al, 2012), utlizando a fala encadeada e frases foneticamente balanceadas (em inglês), que foram estandardizados para avaliar indivíduos com DL (Stewart et al,1997;Langelveld et al, 2000;Merati et al, 2005;Ludlow et al, 2008) e ajudam a estabelecer sinais e sintomas vocais, como, por exemplo: tempo das quebras de voz (sonoridade), duração e localização dos picos e interrupção da frequência e dos segmentos aperiódicos (Sapienza et al, 1998 (Benninger et al, 2001;Baylor et al, 2005).…”
Section: Dysphonia Association)unclassified